IMAGE SEGMENTATION: A WATERSHED TRANSFORMATION ALGORITHM - Belaid, Lamia Jaafar; Mourou, Walid (Image Analysis and Stereology, 2011)
The goal of this work is to present a new method for image segmentation using mathematicalmorphology. The approach used is based on the watershed transformation. In order to avoid an oversegmentation, we propose to adapt the topological gradient method. The watershed transformation combined with a fast algorithm based on the topological gradient approach gives good results. The numerical tests obtained illustrate the efficiency of our approach for image segmentation.